ANTECEDENTS OF CUSTOMER SATISFACTION AND ITS IMPACT ON CUSTOMER LOYALTY AT SHELL JAKARTA GAS STATION - Moudy Fitria Respati; Beby Karina Fawzeea; Yeni Absah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The high demand for fuel oil (BBM) in Indonesia, which is dominated by the transportation sector, encourages Shell gas stations to innovate in their services and product quality. Although Shell gas stations are known for their good reputation, fuel quality issues at Pertamina gas stations, such as adulteration, have made many customers switch to Shell. This study shows that customers are increasingly considering fuel quality and customer service in choosing gas stations, and the challenges faced in the Shell Go+ loyalty program are important factors in retaining customers in a competitive market. This study aims to determine and analyze the effect of brand image and customer experience on customer loyalty with customer satisfaction as an intervening variable at Shell gas stations in Jakarta City. The sample in this study were people in Jakarta City who had purchased and used Shell fuel at least 2 times a month. The sampling technique in this study was the accidental sampling technique with 110 respondents. The data analysis method used Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that Brand Image had a positive and significant effect on Customer Loyalty and Customer Satisfaction. Meanwhile, Customer Experience has a positive and significant effect on Customer Loyalty and Customer Satisfaction. Finally, Customer Satisfaction has a significant effect in mediating the relationship between Brand Image and Customer Experience on Customer Loyalty.